RELATIONSHIP BETWEEN SELECTED SOMATIC PARAMETERS AND SOCIO-CULTURAL CHARACTERISTICS OF CZECH ADULT POPULATION (Fiep Bulletin - online, 2013)
In this article are presented results of testing 569 Czech adult people (273 males and 296 females) older than 18 years. In this contribution there are discussed results in 5 physical development parameters: body height, body weight, BMI, fat tissue percentage and waist hips rate, which were measured by machine Inbody 720. By questionnaire were learned parameters of life status and education. Presented results show rather negative trends. Parameters of body weight, BMI, fat tissue percentage and waist hips rate seem to be mutually connected. Body weight increases according higher age in all watched periods, both in groups of males and of females, too, though the body height decreases. This influences also BMI, when most of male groups and two oldest female groups are of overweight. Similarly results can be seen in parameters of fat tissue percentage and waist hips rate. Those who are single or possess good education level have better results in these watched parameters.
Keywords: somatic parameters; Czech adult population; socio-cultural characteristics